Knowledge and Perception of Premarital Screening within Young Adults: Study at STIKES Bhakti Husada Mulia - Kunawati Tungga Dewi; Novi Paramitasari MS; Rochmanita Sandya Afindaningrum (Viva Medika, 2025)
Premarital screening (PMS) is a screening procedure offered to couples planning to marry to check for genetic and infectious disorders in order to reduce the risk of disease transmission to their offspring. This preventative intervention will help to reduce the incidence of specific genetic illnesses related with marriage. The primary objective of this study was to describe young adults’ knowledge and perceptions about premarital screening in a university setting. This cross-sectional study utilized an online survey to collect data from midwifery students at STIKES Bhakti Husada Mulia Madiun. Statistical analysis was conducted using Chi-square tests. The study found a significant association between knowledge level and age group with p-value of 0.018 (p < 0.05) and Cramér's V of 0.26, indicating a moderate effect. Additionally, a significant association was found between perception level and age with p-value = 0.045 and Cramér's V of 0.21, indicating moderate effect. 37% of respondents learned about PMS through formal education, 33% from social media, 24% from health services, and the others from television and friends. The majority of midwifery students had an adequate knowledge and perception of PMS. The findings highlight the significance of formal education and health services in raising awareness of PMS. This study emphasizes the possibility of premarital screening as a preventive health application that could help to reduce genetic and infectious diseases in future generations, with implications for public health policies and interventions, including marriage health education.